2021
DOI: 10.1111/pbaf.12285
|View full text |Cite
|
Sign up to set email alerts
|

The use of short‐term debt by general‐purpose governments

Abstract: This paper analyzes local government use of short-term debt. Though long-term debt, largely used for capital projects, is relatively well-researched, predictors for the use of short-term debt need to be further developed. We hypothesize that governments with limited cash reserves and expenditure flexibility are more likely to use short-term debt. Further, we expect that governments use short-term debt as an instrument to manage market timing for longterm debt. Using a heterogeneous sample of New York local gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Prior research (Lofton & Kioko, 2021;Su & Hildreth, 2018) suggested that the decision to issue short-term borrowing is likely a two-step process. First, a government decides whether short-term borrowing should occur.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research (Lofton & Kioko, 2021;Su & Hildreth, 2018) suggested that the decision to issue short-term borrowing is likely a two-step process. First, a government decides whether short-term borrowing should occur.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this work evaluates the impact of ETC on short-term borrowing. Prior studies have used cash management notes (Su & Hildreth, 2018) and a broader array of short-term notes (Lofton & Kioko, 2021; as measurements of short-term borrowing, but these only capture market transactions. Governments may also borrow from nonmarket sources, such as their state government, or transfer between funds.…”
Section: Financial Slack Resource Of Excess Taxing Capacitymentioning
confidence: 99%
See 3 more Smart Citations